A lithium iron phosphate positive electrode material and its preparation method and application
By using an iron-based metal organic framework as a multifunctional source material, a nano-based three-dimensional carbon mesh layer is formed, which solves the problem of poor electrode ion conductivity during high current charging and discharging of lithium iron phosphate positive electrode materials, and achieves high conductivity and large-scale discharge capabilities, which are suitable for large-scale production.
Patent Information
- Application Number
- CN202411780521.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The existing lithium iron phosphate positive electrode materials have poor electrode conductivity during charging and discharging of large currents, which limits their large-scale application.
An iron-based metal organic framework is used as the iron source, carbon source, N source and S source of lithium iron phosphate positive electrode material, and a nano-3D carbon network layer is formed through high temperature carbonization to improve the conductivity of ions and electrons.
The conductivity and large-scale discharge capacity of lithium iron phosphate are significantly improved, and the discharge specific capacity of 0.2C reaches 165.3mAh/g, which meets the high-performance requirements, simplifies the preparation process and reduces production costs.
Smart Images

Figure CN119218969B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion battery positive electrode materials, and specifically relates to a lithium iron phosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium iron phosphate is currently a commonly used positive electrode material for lithium-ion batteries. Lithium iron phosphate has good lattice stability, and the insertion and extraction of lithium ions have little effect on the lattice, so it has good reversibility. It can be charged and discharged more than 2,000 times under 100% depth of discharge (DoD) conditions. However, the main disadvantage of lithium iron phosphate is that the electrode ion conductivity is poor, which is not suitable for large current charging and discharging, thus limiting its large-scale application.
[0003] The patent with patent announcement number CN116022762B discloses lithium iron phosphate positive electrode materials and their preparation methods and applications. The patent mixes and grinds the iron source, phosphorus source and lithium source, and then sintering them under a protective atmosphere; the iron source includes Fe-MOF material. The invention uses the rich porosity and unique hierarchical porous structure of MOFs materials as a template to prepare MOFs-based lithium iron phosphate positive electrode materials, which can achieve the effects of grain refinement, ensuring particle uniformity, and improving conductivity. However, the metal organic framework used in this patent and the prior art has a single function, and the prepared lithium iron phosphate positive electrode material still has the disadvantages of poor performance such as discharge specific capacity. Summary of the invention
[0004] In order to solve the disadvantage that the lithium iron phosphate positive electrode material prepared by the prior art in the background technology still has poor performance such as discharge specific capacity, the purpose of the present invention is to provide a lithium iron phosphate positive electrode material and a preparation method and application thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing a lithium iron phosphate positive electrode material comprises the following steps:
[0007] After the iron source, phosphorus source and lithium source are mixed and ground, they are sintered in an inert atmosphere and cooled to room temperature to obtain a lithium iron phosphate positive electrode material; the iron source is an iron-based metal organic framework, and the organic ligands of the iron-based metal organic framework are composed of 2-mercaptoimidazole and polycarboxyl ligands.
[0008] Among them, the iron source, phosphorus source and lithium source are mixed in a molar ratio of Fe:P:Li=(1-1.2):1:1.
[0009] Metal-organic framework materials tend to form well-dispersed, nano-sized materials when carbonized at high temperatures. The three-dimensional carbon network layer coated on the surface of lithium iron phosphate has a complete and uniform full-carbon coating and a continuous carbon film framework, which constructs a good conductivity path for electrons and a favorable porous diffusion structure for lithium ions. It can improve the conductivity of ions and electrons, effectively improve the conductivity of lithium iron phosphate, and improve its high-rate discharge capability.
[0010] 2-Mercaptoimidazole and polycarboxyl ligands are used as organic ligands of an iron-based metal organic framework. By using a solvothermal method, the carboxyl groups of the polycarboxyl ligands are deprotonated to form carboxylate ions. The iron ions can be connected to the nitrogen atoms of 2-mercaptoimidazole and the oxygen atoms of the polycarboxyl ligands through coordination bonds, thereby preparing an iron-based metal organic framework containing N and S. The iron-based metal organic framework can be used as an iron source, a carbon source, a N source and a S source for lithium iron phosphate positive electrode materials.
[0011] Using an iron-based metal-organic framework as the iron source can improve the dispersion of the element and reduce agglomeration; and the metal element Fe is "anchored" on the organic ligand. Since the microscopic size of the iron-based metal-organic framework is at the nanometer level, it can induce the prepared lithium iron phosphate particles to have a smaller particle size, shorten the lithium ion diffusion distance, and accelerate the diffusion rate, thereby improving the electrochemical performance of the lithium iron phosphate positive electrode material.
[0012] Using an iron-based metal organic framework as a carbon source, the organic ligand can be carbonized after high-temperature calcination and evenly coated on the positive electrode material as a carbon source, ensuring the uniformity of the coating and thereby improving the electrochemical performance of the positive electrode material.
[0013] Using iron-based metal organic frameworks as N and S sources, chemical bonds such as CS and CN can be generated between N and S and C in organic ligands, thereby affecting the local electron density of carbon materials, generating different types of defects and vacancies, forming more electrochemical reaction active sites, facilitating the embedding and de-embedding of lithium ions, and improving the electrochemical performance of lithium iron phosphate cathode materials. Moreover, using iron-based metal organic frameworks as N and S sources, the N and S sources have better dispersion, and can form a more uniform network structure, thereby improving the transmission capacity of lithium ions.
[0014] Further, the phosphorus source includes one or more combinations of diammonium phosphate, ammonium hydrogen phosphate and ammonium phosphate.
[0015] Further, the lithium source includes a combination of one or more of lithium carbonate, lithium chloride, lithium nitrate, lithium fluoride, lithium sulfate and lithium hydroxide.
[0016] Furthermore, the mixed grinding is ball milling, the ball milling time is 4-12 hours, and the rotation speed of the ball mill is 2000-3000rpm.
[0017] Furthermore, the inert atmosphere is any one of nitrogen, argon and helium.
[0018] Furthermore, the sintering time is 8-13 hours and the temperature is 600-900°C.
[0019] Further, the preparation steps of the iron source are as follows:
[0020] The iron salt, 2-mercaptoimidazole and polycarboxyl ligand are dissolved in a 90%-95% by volume DMF aqueous solution to obtain a mixed solution, and the mixture is subjected to magnetic stirring for 0.8-1.5 hours, reacted at 150° C. for 12-15 hours, cooled to room temperature, washed alternately with DMF and methanol for 3 times, dried, and ground to obtain an iron source.
[0021] Among them, the molar ratio of iron salt, 2-mercaptoimidazole and polycarboxyl ligand is 1:(8-10):1.
[0022] Furthermore, the iron salt is any one of ferric chloride, ferric nitrate and ferric sulfate.
[0023] Furthermore, the concentration of the iron salt in the mixed solution is 4 g / L.
[0024] Furthermore, the polycarboxyl ligand is terephthalic acid or trimesic acid.
[0025] A lithium iron phosphate positive electrode material is prepared by the preparation method of the lithium iron phosphate positive electrode material described in any one of the above contents.
[0026] An application of the lithium iron phosphate positive electrode material described above in a lithium ion battery.
[0027] Beneficial effects of the present invention:
[0028] 1. The battery made of the lithium iron phosphate positive electrode material prepared by the present invention has a 0.2C discharge specific capacity of more than 165.3 mAh / g, has excellent electrochemical properties, and meets the requirements of high-performance lithium iron phosphate positive electrode materials required on the market.
[0029] 2. The present invention uses an iron-based metal organic framework as the iron source, carbon source, N source and S source of the lithium iron phosphate positive electrode material, which can simplify the entire preparation process and avoid additional mixing steps, thereby reducing production costs and improving production efficiency, and is suitable for large-scale production.
[0030] 3. The present invention is beneficial to the preparation of lithium manganese iron phosphate positive electrode materials with good electrochemical performance by accurately controlling the amount of iron source added. Too much or too little iron source added will affect the overall performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The present invention will be further described below in conjunction with the accompanying drawings.
[0032] Figure 1This is a scanning electron microscope photograph of the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Preparation Example 1
[0035] The preparation steps of the iron source of this preparation example are as follows:
[0036] 0.4 g of Fe 2 (SO 4 ) 3 , 0.8 g of 2-mercaptoimidazole and 0.17 g of terephthalic acid were dissolved in 100 mL of 90% by volume DMF aqueous solution to obtain a mixed solution. The mixture was stirred magnetically for 0.8 h and reacted at 150 ° C for 12 h. The mixture was cooled to room temperature, washed alternately with DMF and methanol for 3 times, dried, and ground to obtain an iron source.
[0037] Preparation Example 2
[0038] The preparation steps of the iron source of this preparation example are as follows:
[0039] 0.24g of , 0.9 g of 2-mercaptoimidazole and 0.17 g of terephthalic acid were dissolved in 60 mL of 92% by volume DMF aqueous solution to obtain a mixed solution. The mixture was magnetically stirred for 1.1 h and reacted at 150 ° C for 13 h. The mixture was cooled to room temperature, washed alternately with DMF and methanol for 3 times, dried, and ground to obtain an iron source.
[0040] Preparation Example 3
[0041] The preparation steps of the iron source of this preparation example are as follows:
[0042] 0.16 g of FeCl 3 , 1 g of 2-mercaptoimidazole and 0.21 g of trimesic acid were dissolved in 40 mL of 95% by volume DMF aqueous solution to obtain a mixed solution. The solution was stirred magnetically for 1.5 h and reacted at 150 ° C for 15 h. The solution was cooled to room temperature, washed alternately with DMF and methanol for 3 times, dried, and ground to obtain an iron source.
[0043] Preparation Example 4
[0044] The preparation steps of the iron source of this preparation example are as follows:
[0045] 0.4 g of Fe2 (SO 4 ) 3 , 0.66 g of 2-methylimidazole and 0.17 g of terephthalic acid were dissolved in 100 mL of 90% by volume DMF aqueous solution to obtain a mixed solution. The mixture was stirred magnetically for 1.1 h at 150 ° C for 13 h, cooled to room temperature, washed alternately with DMF and methanol for 3 times, dried, and ground to obtain an iron source.
[0046] Preparation Example 5
[0047] The preparation steps of the iron source of this preparation example are as follows:
[0048] 0.4 g of Fe 2 (SO 4 ) 3 , 0.17 g of terephthalic acid was dissolved in 100 mL of 90% by volume DMF aqueous solution to obtain a mixed solution, the mixture was magnetically stirred for 1.1 h, reacted at 150 ° C for 13 h, cooled to room temperature, washed three times with DMF and methanol alternately, dried, and ground to obtain an iron source.
[0049] Preparation Example 6
[0050] The preparation steps of the iron source of this preparation example are as follows:
[0051] 0.4 g of Fe 2 (SO 4 ) 3 , 0.21 g of trimesic acid was dissolved in 100 mL of 90% by volume DMF aqueous solution to obtain a mixed solution, and the solution was subjected to magnetic stirring for 1.1 h, reacted at 150 ° C for 13 h, cooled to room temperature, washed three times with DMF and methanol alternately, dried, and ground to obtain an iron source.
[0052] Example 1
[0053] This embodiment provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:
[0054] The iron source prepared in Preparation Example 1, ammonium dihydrogen phosphate and lithium chloride were mixed in a molar ratio of Fe:P:Li=1:1:1, ball-milled at 2000 rpm for 4 h, sintered in a nitrogen atmosphere for 8 h at a temperature of 600°C, and cooled to room temperature to obtain a lithium iron phosphate positive electrode material.
[0055] Example 2
[0056] This embodiment provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:
[0057] The iron source prepared in Preparation Example 2, ammonium hydrogen phosphate and lithium nitrate were mixed in a molar ratio of Fe:P:Li=1.1:1:1, ball-milled at 2500rpm for 8h, sintered in an argon atmosphere for 12h at a temperature of 900°C, and cooled to room temperature to obtain a lithium iron phosphate positive electrode material.
[0058] Example 3
[0059] This embodiment provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:
[0060] The iron source prepared in Preparation Example 3, ammonium dihydrogen phosphate and lithium fluoride were mixed in a molar ratio of Fe:P:Li=1.2:1:1, ball-milled at 3000 rpm for 12 h, sintered in a helium atmosphere for 13 h at a temperature of 800°C, and cooled to room temperature to obtain a lithium iron phosphate positive electrode material.
[0061] Comparative Example 1
[0062] This comparative example provides a method for preparing a lithium iron phosphate positive electrode material. Compared with Example 1, the difference is that the iron source in Example 1 is replaced by the product prepared in Preparation Example 4, and the remaining raw materials and steps are the same as Example 1.
[0063] Comparative Example 2
[0064] This comparative example provides a method for preparing a lithium iron phosphate positive electrode material. Compared with Example 1, the difference is that the iron source in Example 1 is replaced by the product prepared in Preparation Example 5, and the remaining raw materials and steps are the same as Example 1.
[0065] Comparative Example 3
[0066] This comparative example provides a method for preparing a lithium iron phosphate positive electrode material. Compared with Example 1, the difference is that the iron source in Example 1 is replaced by the product prepared in Preparation Example 6, and the remaining raw materials and steps are the same as Example 1.
[0067] Comparative Example 4
[0068] This comparative example provides a method for preparing a lithium iron phosphate positive electrode material. Compared with Example 1, the difference is that the "Fe: P: Li = 1:1:1 mixture" in Example 1 is replaced by "Fe: P: Li = 0.9:1:1 mixture", and the remaining raw materials and steps are the same as Example 1.
[0069] Comparative Example 5
[0070] This comparative example provides a method for preparing a lithium iron phosphate positive electrode material. Compared with Example 3, the difference is that the "Fe:P:Li=1:1:1 mixture" in Example 3 is replaced by "Fe:P:Li=1.3:1:1 mixture", and the remaining raw materials and steps are the same as Example 3.
[0071] Comparative Example 6
[0072] This preparation example provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:
[0073] Iron oxide, diammonium phosphate and lithium chloride were mixed in a molar ratio of Fe:P:Li=1:1:1, ball-milled at 2000rpm for 4h, sintered in a nitrogen atmosphere for 8h at a temperature of 600°C, then 0.1mol of glucose was added and heat treated at 600°C for 4h, and cooled to room temperature to obtain a lithium iron phosphate positive electrode material.
[0074] The lithium iron phosphate positive electrode material prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 6 was mixed with carbon black and PVDF in a mass ratio of 80:10:10 to prepare a slurry; the uniformly mixed slurry was coated on an aluminum foil and vacuum dried at 100°C for 4 hours; the dried aluminum foil was rolled with a roller press, and then cut and weighed; then a 2032 button battery was assembled in an argon atmosphere vacuum glove box, with lithium iron phosphate as the positive electrode, a metal lithium sheet as the negative electrode, a Celgard2300 diaphragm, and an electrolyte of 1 mol / L LiPF 6 / (EC+DMC+EMC)(volume ratio 1:1:1); then seal the battery with a sealing machine and let it stand for 7-8h. The battery performance test was carried out on the Wuhan Blue Electric Battery Test System, and constant current charge and discharge tests were carried out in the voltage range of 2.5-4.2V. The test results are shown in Table 1.
[0075]
[0076] It can be seen from Table 1 that the performance of the batteries prepared in Examples 1 to 3 is better than that of the batteries prepared in Comparative Examples 1 to 6. Comparative Example 1 does not contain the S element, the electrochemical reaction active sites are reduced, and the electrochemical performance is lower than that of Example 1; Comparative Example 2 does not contain the S element and the N element, the electrochemical reaction active sites are further reduced, and the electrochemical performance is lower than that of Example 1; Comparative Example 3 is similar to Comparative Example 2, and neither contains the S element and the N element, but the organic ligand used in Comparative Example 3 is trimesic acid, and Comparative Example 2 uses terephthalic acid. The carboxyl content of the polycarboxyl ligand in Comparative Example 3 is high, so that the iron-based metal organic skeleton has a specific morphology, which can induce the preparation of a lithium iron phosphate positive electrode material with a fine particle size, the lithium iron phosphate particle size is smaller, the lithium ion diffusion distance is shortened, the diffusion rate is accelerated, and the electrochemical performance of the lithium iron phosphate positive electrode material is improved; Comparative Example 4 and Comparative Example 5 have too little or too much iron source added, and the battery performance of both is reduced compared with Example 1 and Example 3, indicating that the content used in the present invention is the optimal amount, and the best performance battery can be prepared; Comparative Example 6 uses ordinary carbon source and iron source, and the prepared battery performance is the worst compared with other embodiments and comparative examples.
[0077] from Figure 1 It can be seen that the lithium iron phosphate positive electrode material of the present invention is successfully prepared, the particles are uniform and the surface is smooth.
[0078] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0079] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: After the iron source, phosphorus source and lithium source are mixed and ground, they are sintered in an inert atmosphere and cooled to room temperature to obtain a lithium iron phosphate positive electrode material; the iron source is an iron-based metal organic framework, and the organic ligand of the iron-based metal organic framework is composed of 2-mercaptoimidazole and polycarboxyl ligands; The iron source, phosphorus source and lithium source are mixed in a molar ratio of Fe:P:Li=(1-1.2):1:
1.
2. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: The phosphorus source includes one or more combinations of ammonium dihydrogen phosphate, ammonium hydrogen phosphate and ammonium phosphate; the lithium source includes one or more combinations of lithium carbonate, lithium chloride, lithium nitrate, lithium fluoride, lithium sulfate and lithium hydroxide.
3. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: The mixed grinding is ball milling, the ball milling time is 4-12 hours, and the ball milling speed is 2000-3000rpm.
4. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: The inert atmosphere is any one of nitrogen, argon and helium; the sintering time is 8-13h, and the temperature is 600-900°C.
5. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: The steps for preparing the iron source are as follows: The iron salt, 2-mercaptoimidazole and polycarboxyl ligand are dissolved in a 90%-95% by volume DMF aqueous solution to obtain a mixed solution, and the mixture is subjected to magnetic stirring for 0.8-1.5 hours, reacted at 150° C. for 12-15 hours, cooled to room temperature, washed, dried and ground to obtain an iron source.
6. The method for preparing a lithium iron phosphate positive electrode material according to claim 5, characterized in that: The molar ratio of iron salt, 2-mercaptoimidazole and polycarboxyl ligand is 1:(8-10):
1.
7. The method for preparing a lithium iron phosphate positive electrode material according to claim 5, characterized in that: The iron salt is any one of iron chloride, iron nitrate and iron sulfate; the concentration of the iron salt in the mixed solution is 4 g / L; and the polycarboxyl ligand is terephthalic acid or trimesic acid.
8. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material is prepared by the preparation method of any one of claims 1 to 7.
9. Use of the lithium iron phosphate positive electrode material according to claim 8 in a lithium ion battery.
Citation Information
Patent Citations
Lithium iron phosphate positive electrode material and preparation method and application thereof
CN116022762B
Lithium iron phosphate positive electrode material and preparation method and application thereof
CN116022762A
Double-doped coated lithium iron phosphate positive electrode material, preparation method thereof and lithium battery
CN119008918A